Analisis Karakter Kerja Keras dalam Pembelajaran Tematik di Sekolah Dasar - Nursakinah; Putri Fadillah; Irma Widya Ningsih; Junaidi Junaidi (Cahaya Ilmu Cendekia Publisher, 2022)
Research objectives: This study aims to find out how thematic learning can become meaningful for students and the thematic learning outcomes of third-grade elementary school students. Methodology: This research is qualitative research. By using a case study design. The research subjects were the educators who were observed and 10 students in grade III elementary schools who were obtained using a purposive sampling technique. Main findings: Thematic learning in elementary schools has strengths and increases students' hard work in learning. Novelty/Originality of this study: Thematic learning is able to provide improvement and positive influence in all learning components